Amostragem diurna versus noturna de ácaros (Arachnida: Acari) associados a Genipa americana L. (Rubiaceae) - Silva, Paulo Vittor Parecis [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Community composition and abundance of plant and edaphic mites throughout nighttime are poorly known by the fact that studies are usually conducted only during the day. Thus, the objective of this study was to compare the diurnal and nocturnal community evaluating the possible influences of plant mites in the litter community. The research was conducted monthly from July 2012 to June 2013 in three areas in the municipality of São José do Rio Preto, SP. Twenty-one adult trees were selected for sampling in daytime and nighttime, and 10 leaves / tree / sample period were collected. In addition, part of the accumulated litter in the base of three Brazilian genipap plants in each of the three areas was collected. The areas were sampled always in the same order, Arboretum, Forest Grove 1 and Forest Grove 2, with daytime samplings between 8am and 11am and the evening samplings between 21pm and 23pm. 10,117 mites were collected during the day and 7,632 at night, distributed in 60 species. Euseius citrifolius Denmark & Muma and Euseius concordis Chant showed higher abundances in the daytime, while Agistemus floridanus Gonzalez presented a greater tendency to forage leaves at night. In leaf litter accumulated at the base of the Brazilian genipaps sampled, 4,168 mites were recorded during the day and 3,153 at night, identified in 95 species. The two species analyzed in this environment, Amblyseius aerialis Muma and Iphiseiodes saopaulus Denmark & Muma, have no significant differences in mean abundances between the two periods. The plant community showed no similarity with the litter community. Regarding the structure of the community, there was no difference between areas or between periods. The achieved results confirm that some species of mites have a different pattern of distribution between the periods studied, but the litter associated with genipap not act as refuge of these mites. Thus, the species that had lower abundance in the leaves in ...

A composição da comunidade e a abundância de ácaros plantícolas e edáficos ao longo do período noturno são pouco conhecidas pelo fato dos estudos serem conduzidos apenas durante o dia. Dessa forma, o objetivo do trabalho foi comparar a comunidade diurna e noturna avaliando as possíveis influências da acarofauna do folhedo na comunidade plantícola. A pesquisa foi desenvolvida mensalmente no período de julho de 2012 a junho de 2013 em três áreas no município de São José do Rio Preto, SP. Vinte e uma árvores adultas foram selecionadas para as amostragens no período diurno e noturno, e foram coletadas 10 folhas/árvore/período amostrado. Além disso, foi coletado parte do folhedo acumulado na base de três plantas de jenipapo, em cada uma das três áreas. As áreas foram amostradas sempre na mesma ordem, Arboreto, Bosque 1 e Bosque 2, com as amostragens diurnas entre 8h e 11h e as noturnas entre 21h e 23h. Foram coletados 10.117 ácaros durante o dia e 7.632 durante a noite, distribuídos em 60 espécies. Euseius citrifolius Denmark & Muma e Euseius concordis Chant apresentaram maiores abundâncias médias no período diurno, enquanto que Agistemus floridanus Gonzalez apresentou uma maior tendência de forragear as folhas no período noturno. No folhedo acumulado na base das plantas amostradas foram registradas 4.168 ácaros durante o dia e 3.153 durante a noite, identificados em 95 espécies. As duas espécies analisadas nesse ambiente, Amblyseius aerialis Muma e Iphiseiodes saopaulus Denmark & Muma, não apresentaram diferenças significativas entre abundâncias médias entre os dois períodos. A comunidade plantícola não apresentou similaridade com a comunidade do folhedo. Com relação à estrutura da comunidade, não houve diferença entre as áreas nem entre períodos. Os resultados atingidos confirmam que algumas espécies de ácaros apresentam um padrão de distribuição diferente entre os períodos estudados, porém ...
Keywords: Ecologia; Ácaro; Ácaro de plantas - São José do Rio Preto; Jenipapo; Mites